Pattern of care and survival of anaplastic lymphoma kinase rearranged non–small cell lung cancer (ALK+ NSCLC) in an Australian Metropolitan Tertiary Referral Centre: A retrospective cohort analysis. Issue 5 (19th April 2018) - Itchins, Malinda; Hayes, Sarah A.; Gill, Anthony J.; Cooper, Wendy; O'Connell, Rachel; Howell, Viive M.; Clarke, Stephen J.; Pavlakis, Nick
Abstract: Aim: To report on the pattern of care and survival of anaplastic lymphoma kinase rearranged non–small cell lung cancer ( ALK+ NSCLC) in a real‐world retrospective cohort from an Australian tertiary referral center. Methods: Individuals with a pathological diagnosis of ALK+ NSCLC via immunohistochemistry and fluorescence in situ hybridization and a radiological diagnosis of stage IV disease were eligible. Patients were identified via the Pathology Department specimen database and electronic patient chart review. Data were collected and analyzed for baseline demographics, radiological pattern of disease and response to treatment, treatment sequencing, toxicity and survival. Results: Thirty‐five patients were identified over a 7‐year period from 2010 to 2016 and followed for a median of 23 months. Median overall survival (OS) in the entire cohort was immature at data cut, 46.0 months (95% confidence interval [CI], 22.53–69.47 months), with the longest surviving patient was alive 62.1 months since diagnosis. Objective radiological response rate overall across six potential treatments and six treatment lines (range 1–6) was 58.2%. Almost 50% received at‐least two lines of ALK inhibitor therapy with median OS in this group estimated to be 53.4 months (95% CI, 35.1 months–not reached). Toxicity was manageable with a low rate of ≥ grade 3 toxicity ( n = 7). Forty‐eight percent relapsed within the CNS and 43% overall died due to CNS progression. In those with CNS diagnosis at baseline and/or progression within the CNS ( n = 32), median OS was also 46.0 months (95% CI, 24.22–66.78 months). Conclusion: This retrospective cohort analysis of a single tertiary institution experience in treating ALK+ NSCLC demonstrates impressive OS and the importance and impact of careful management of CNS disease in this patient population.